2020
DOI: 10.1016/j.heliyon.2020.e04450
|View full text |Cite
|
Sign up to set email alerts
|

Parametric sensitivity analysis for a natural gas fueled high temperature tubular solid oxide fuel cell

Abstract: For more than the last two decades, there has been research going on to develop advanced energy technologies involving minimum environmental pollution, to replace the conventional fossil energy systems. Solid oxide fuel cells (SOFCs) are one of the most promising, eco-friendly and efficient means for the generation of electricity to meet the future energy requirements. This research work focuses on the parametric sensitivity analysis for natural gas fueled high temperature tubular SOFC. Firstly, for the tubula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Solid oxide fuel cell (SOFC) is regarded as one of the most promising new energy technologies 1 due to its high fuel flexibility, 2,3 low environmental pollution, 4 small volume, 5 no Carnot cycle restriction for power generation efficiency, 6 and can be combined with a gas turbine for power generation 7 . Its performance has been comprehensively studied, 8‐12 and it has been applied on a certain scale 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Solid oxide fuel cell (SOFC) is regarded as one of the most promising new energy technologies 1 due to its high fuel flexibility, 2,3 low environmental pollution, 4 small volume, 5 no Carnot cycle restriction for power generation efficiency, 6 and can be combined with a gas turbine for power generation 7 . Its performance has been comprehensively studied, 8‐12 and it has been applied on a certain scale 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The natural gas consisted of 63% CH 4 and 37% CO. The carbon forms on nickel-based anodes via the cracking of methane (eqn (14)) and the Boudouard reaction (eqn (15)):…”
Section: Thermodynamic Calculationsmentioning
confidence: 99%
“…Currently, significant research is focused on adapting and advancing Ni-based anodes to improve their resistance against carbon deposition in the presence of hydrocarbon fuels. 14 Ceria-based anodes exhibit mixed ionic and electronic conductivity (MIEC) and improved electro-catalytic activity at low temperatures via the reduction of Ce 4+ to Ce 3+ . 15 This reduction, described using the following equation, causes n-type defects and the formation of oxygen vacancies (O ν ) that also gives rise to mixed conduction:where O × O represents oxygen in the ceria lattice, represents a vacancy created by oxygen (with a 2+ charge) and e′ is an electron.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the problems solved by numerical methods include electrochemical process modeling, collector design, performance modeling, the influence of electrode microstructure, thermal stress analysis, and the development of new SOFC structural elements [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…When analyzing publication activity from 2021 to 2024, it was revealed that the interest of researchers modeling SOFCs is aimed at studying the operation of a fuel cell using various types of organic and inorganic fuels, biofuels, and various agricultural and industrial wastes [12,14,16,27,38,39].…”
Section: Introductionmentioning
confidence: 99%